Work and Organizations - Kinney, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is intended to provide you with a broad base of both theoretical and applied knowledge regarding the nature of work and organizations in American, and world, society. In order to achieve this, the course will progress through several general topic areas: 1)the foundations of the study of work and organizations, including fundamental concepts, issues, and theories on work/organizations; 2)the operational existence of organizations and the impact of their operation on our lives (e.g., the culture of the workplace, socialization into a working life, etc.), and; 3)critical perspectives on living a life devoted to work in the organizational world (e.g., the extent of organizational control in our lives, conflict in organizations, job satisfaction/dissatisfaction, politics in the workplace, etc.).